Education for sustainability in higher education: The teacher’s rolein shaping the administrator - Becker, Deisi Viviani; Ávila, Lucas Veiga; Nascimento, Luis Felipe Machado; Madruga, Lúcia Rejane da Rosa Gama (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This study aims to analyze how teachers of the undergraduate program in a HEI, their teaching role with the requirements of education for sustainability in education. The study is classified as aqualitative, exploratory, anchored in a semi structured script. We interviewed 13 teachers Administration Course, which have a BA in Business Administration, working in a private institution, among the 44 teachers who work in the course, covering all curriculum components. Among the 13 teachers, not all consider themselves prepared to work with the theme and most of them unaware of the education ministry’s guidelines and regulations that deals with it. Based on the results, it is emphasized that the coursedevelops new perspective on the theme of sustainability, fostering the creation of the research group, hands-on activities related directly to education for sustainability in addition to their discussion on all subjects.